The Softball Solution: Female Workers, Male Managers and the Operation of Paternalism at Westclox, 1923-60 - Sangster, Joan (Labour/Le Travailleur, 1993)
This article uses a case study of an Ontario factory manufacturing clocks and watches to explore the way in which industrial paternalism was used as an industrial relations strategy by both management and workers. I argue that paternalism, in this case an amalgam of 19th-century traditional paternalism and 20th-century welfare capitalism, was premised on unequal economic relations, and on the ideological hegemony of management, but it was also, very importantly, a negotiated process in which workers participated in order to secure better working conditions and wages, respect and dignity. Westclox used benefit plans, sports teams, a company paper, as well as flexibility in work supervision and internal promotions to garner the loyalty of its workers. Paternalism was also gendered: it was justified with reference to the sexual division of labour and with metaphors of a male-headed family. Though attractive to some workers, paternalism also had it weaknesses; both men and women questioned paternalism when management failed to live up to its side of a negotiated bargain.